(3GdJMhd GdOjebQGWi h JCKjQg Ydi GdGSJbQGQ GdSjGSi (B: s (3OQGSI ebGQfI (B/ s - (3QjgGe eUWai eLOi UahJ QDhas; (3eMeO eMeO HOQGfs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2019)
(3JMGhd gPg GdOQGSI QUO h JMdjd XGgQI GdJMhd GdOjebQGWi h YdGbJgG HCMOGK GdQHjY GdYQHi(B: (3Jdc GdehLI GdKhQjI GdJi fJL YfgG GdYOjO ef GdJOGYjGJ GdSjGSjI h GdbGfhfjI h JSHHJ ai GdEWGMI HGdGSJbQGQ GdSjGSi dYOO ef GdOhd GdYQHjI(B. (3h GgJeJ GdOQGSI HGdJQcjR Ydi eaghe GdOjebQGWjI h UhQgG(B: (3h ef Ke eaghe GdJMhd GdOjebQGWi h eQGMdg h CfeGWg h GdYhGed GdeMaRI dg(B: (3ef NdGd OQGSI ebGQfI dJLQHJi GdJMhd GdOjebQGWi aj cdkG ef QhSjG fehPLkG Yf ChQhHG GdTQbjI h eUQ fehPLkG Yf GdYGde GdYQHi(B: (3ddhbha Ydi GdaQhb Hjf GdJLQHJjf h GSJNdGU GdOQhS GdeSJaGOI(B. (3h NdUJ GdOQGSI Edi NWhQI OhQ GdYGed GdNGQLi GdeJeKd ai GJLGg GdfXGe GdYGdei h GdOhd GdcHQi fMh aQV fehPL GdOjebQGWjI GddjHQGdjI Ydi GdLejY (B: (3hUd Edi MO GSJNOGe GdbhI ddJNdU ef GdCfXeI GdZjQ OjebQGWjI(B: (3h eG dPdc ef CKQ Ydi eSJbHd GdGSJbQGQ GdSjGSi HGdefWbI GdYQHjI ccds
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdYGe, (B2019s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B534-592s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdbGfhf GdYGes; (3GdJMhd GdOjebQGWis; (3GdKhQIs; (3GdOjebQGWjI GdehLgIs; (3GdaQb Hjf GdSdWhjI hGdTehdjIs; (3eUOQ GdOjebQGWjI aj GdGSdGes; (3eUOQ GdOjebQGWjI YfO GdZQHs; (3GdOjebQGWjI hGdMQjIs; (3GdOjebQGWjI hGdbGfhfs; (3GdOjebQGWjI hGdGfJNGHs; (3JLQHI QhSjG ai GdJMhd GdOjebQGWis; (3GdUhQ GdJbdjOjI hGdOjebQGWjIs; (3eSJbHd GdJMhd GdOjebQGWi GdYQHis; (3JLQHI GdGJMGO GdShajJjs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdYGes